Oncolytic virus as immunotherapy treatment shows efficacy in canine cancer patients - Martín Carrasco, Clara; Delgado Bonet, Pablo; del Castillo, Noemí; Barbero, Alicia; Carrillo Segura, Manuel; de la Riva, Claudia; Muñoz Blanco, Lorena; García Castro, Javier; Perisé Barrios, Ana Judith (TERMIS EU Abstracts, 2025)
The use of oncolytic viruses is an immunotherapy treatment for cancer based in the use of viruses designed to replicate specifically in tumor cells. This innovative approach has even received the approval from the FDA and EMA with Imlygic, an oncolytic virus based in herpex virus, to be used intratumorally in melanoma patients. Other clinical trials are supporting the increasing evidence about the use oncolytic adenoviruses (Ads) as promising immunotherapy agents. Our goal is determine the safety and efficacy of canine Ads to be used intratumorally. We perform a clinical trial treating canine patients with our Ad ICOCAV15.